Quasi-zero-stiffness nonlinear low-frequency vibration isolation metamaterial structure, vibration isolation device and preparation method
By designing a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, and using laser 3D printing technology to create a zither-shaped frame structure, the shortcomings of traditional vibration isolation structures in low-frequency vibration and complex environments are solved, and high-efficiency vibration isolation and long-life life are achieved. Effect.
Patent Information
- Application Number
- CN202411483336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional vibration isolation structures have limitations in terms of low space utilization, poor environmental adaptability, and difficulty in performing high-precision operations in extreme environments. It is difficult to effectively suppress low-frequency vibration and noise, affecting equipment performance and life.
A quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure is designed, adopting a zither-shaped frame structure with consistent size and shape. The vertical and horizontal creases of the frame structure are provided with vertical and horizontal creases, and are formed by laser 3D printing technology. , enhances the vibration damping and energy absorption capacity of the structure, improves vibration isolation performance and adaptability.
It realizes effective vibration isolation and energy dissipation in low-frequency vibration and complex environments, extends the service life of the vibration isolation device, improves the stability and fatigue resistance of the structure, and significantly improves the vibration isolation effect and manufacturing efficiency.
Smart Images

Figure CN119196206A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quasi-zero stiffness vibration isolation, and more specifically to a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, a vibration isolation device and a preparation method thereof. Background Art
[0002] Vibration and sound control are essential and critical for many engineering applications to minimize the adverse and harmful effects caused by unavoidable vibration and noise. In many fields, such as aerospace, aviation, electronic technology and precision instruments, vibration has a significant impact on the performance, stability and life of equipment and systems. Traditional vibration isolation structures absorb and weaken vibration energy through mechanical damping, elastic elements and other methods to reduce interference with equipment. However, with the continuous advancement of technology, these traditional methods have gradually exposed limitations such as low space utilization, poor environmental adaptability and difficulty in performing high-precision operations in extreme or special environments.
[0003] With the increasing demand for efficient and compact vibration isolation in aerospace and electronic equipment, researchers have begun to develop more innovative vibration isolation structures that better meet modern needs. Therefore, it is urgent to design and manufacture a vibration isolation structure that reduces redundant parts and interacts well with the external environment, which has broad application prospects. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention proposes a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, which has excellent performance in suppressing low-frequency longitudinal waves, increasing vibration damping and energy absorption.
[0005] The present invention also proposes a vibration isolation device having the above-mentioned quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure.
[0006] The invention also proposes a method for preparing a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure.
[0007] The technical solution adopted by the present invention is: to provide a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, including at least a pair of kite-shaped frame structures of uniform size and shape and overlapping front and back, wherein the vertical diagonal line of one of the frame structures is provided with a vertical fold, and the horizontal diagonal line of the other frame structure is provided with a horizontal fold.
[0008] After adopting the above structure, the core advantage of the quasi-zero stiffness structure in suppressing low-frequency longitudinal waves lies in its near-zero stiffness characteristics. This near-zero stiffness characteristic enables the structure to effectively absorb and dissipate the energy of low-frequency vibrations within a specific displacement range, avoiding the accumulation and transmission of vibrations, thereby reducing the impact on other components of the system. Especially for low-frequency vibrations, due to their longer wavelengths and more concentrated energy, traditional vibration isolation structures are often difficult to effectively suppress, while the quasi-zero stiffness design of the present invention can meet these challenges with lower stiffness and achieve excellent vibration isolation effects.
[0009] In addition, the introduction of the crease structure further increases the vibration damping capacity of the system. The interaction between the vertical creases and the horizontal creases gradually achieves a balance between the internal pressure and tension of the vertical creases and the horizontal creases, resulting in a quasi-zero stiffness effect and increasing the dissipation path of vibration energy. This multi-dimensional energy absorption method not only enhances the vibration isolation performance of the system, but also delays the fatigue damage of the structure caused by vibration, extending the service life of the vibration isolation device.
[0010] Through the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, the present invention exhibits extremely strong adaptability in a variety of complex environments. Whether it is long-term low-frequency vibration or instantaneous high-amplitude impact, the structure can provide effective vibration isolation and energy dissipation.
[0011] According to an embodiment of the present invention, the frame structure and the vertical fold or the horizontal fold are an integrated structure, which significantly improves the overall reliability and stability, avoids structural weaknesses that may be caused by connectors or assembly processes, and thus reduces the risk of stress concentration and fatigue damage, ensuring that the structure can still maintain its efficient vibration isolation performance under long-term and complex load conditions.
[0012] According to one embodiment of the present invention, the middle part of the vertical fold and / or the horizontal fold has a plurality of "J"-shaped fold units, which are distributed in a zigzag shape, and each of the fold units is of equal size; the ingenious arrangement of the "J"-shaped fold units gives the vibration isolation structure a higher deformation capacity, especially under low-frequency vibration conditions, it can effectively absorb and dissipate vibration energy. The zigzag fold distribution enables the overall structure to produce multi-directional flexible responses when subjected to force, which enables the structure to exhibit excellent vibration isolation performance when dealing with multi-axis vibration.
[0013] According to one embodiment of the present invention, the frame structure is integrally formed with the vertical fold and the horizontal fold respectively by additive manufacturing technology.
[0014] According to an embodiment of the present invention, mass blocks are provided at the upper and lower ends of the frame structure; the mass blocks can change the inertial characteristics of the structure, so that the natural frequency and vibration mode of the structure change. The mass blocks can increase the damping of the structure, reduce the vibration amplitude, and improve the stability and vibration resistance of the structure.
[0015] A vibration isolation device comprises any one of the above-mentioned quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structures.
[0016] According to an embodiment of the present invention, a plurality of the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structures are connected end to end from top to bottom to form a group of vibration isolation structures, and a plurality of groups of the vibration isolation structures are combined to form a vibration isolation device.
[0017] A method for preparing a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure is formed by a laser 3D printing process, comprising the following steps: S1. Control the oxygen content in the forming cavity to be less than 10 ppm; S2, controlling the powder feeding device to feed the 3D printing metal powder to the forming cylinder, and then using the automatic powder spreading device to evenly spread the aforementioned 3D printing metal powder on the forming substrate; S3, controlling the laser scanning to form the 3D printed metal powder on the substrate until it is completely melted, thereby forming a single-layer cross-section of a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure specimen; the laser line energy scanning speed v of the laser used is between 600 mm / s and 1000 mm / s, and the laser power P is set to a constant value of 200 W; S4. After each layer is processed, the forming cavity is lowered by the thickness of one layer of powder. According to the scanning model of the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, steps S2 and S3 are repeated to finally obtain the target sample formed part.
[0018] The preparation method of the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure in the present invention can accurately reproduce this complex geometric shape by building layer by layer, and ensure the integrity of the microstructure and mechanical properties of the material. Therefore, the laser 3D printing process provides an ideal solution for the realization of this difficult structure, which not only overcomes the limitations of traditional processes, but also significantly improves manufacturing efficiency and precision. Laser 3D printing technology has significant advantages in manufacturing such complex metamaterial structures. First, it can accurately control the construction of each layer at high resolution, thereby realizing fine details and embedded structures in complex origami structures. Secondly, laser 3D printing technology allows the use of a variety of metal and alloy materials, which enables the optimization of material properties such as strength, toughness and heat resistance according to specific application requirements. In addition, laser 3D printing technology can accurately control the microstructure of the material by adjusting the process parameters, thereby further optimizing the mechanical properties of the zero stiffness metamaterial. Therefore, in this invention, the vibration isolation structure is manufactured using laser 3D printing technology. This metamaterial is composed of a quasi-zero stiffness unit array. It has excellent performance in suppressing low-frequency longitudinal waves, increasing vibration damping and energy absorption.
[0019] According to one embodiment of the present invention, in step S3, the laser scanning mode is "S-shaped orthogonal" scanning, the laser scanning speed is 600-1000 mm / s; the laser air jump speed is 3000-3500 mm / s; the laser power is 200 W; the scanning interval is 60-80 μm; the quasi-zero stiffness formed part manufactured by the present invention shows four longitudinal band gaps in the observed frequency range, wherein the ranges of the first, second, third and fourth band gaps are 660 Hz-780 Hz, 1120 Hz-1166 Hz, 1167Hz-1330 Hz and 1420 Hz-2570 Hz, respectively. The quasi-zero stiffness formed parts manufactured by laser 3D printing exhibit quasi-zero stiffness characteristics, which enable them to produce low-frequency resonance and can be used for the absorption of low-frequency longitudinal waves.
[0020] According to one embodiment of the present invention, the 3D printed metal powder is gas atomized AlSi7Mg alloy powder, and the particle size range of the powder is 15-53 μm; by utilizing the effects of alloying elements such as Al, Si, and Mg, a uniform structure is obtained under a very high cooling rate of laser processing, and only a weak texture equivalent to an isotropic characteristic is shown, which greatly shortens the manufacturing cycle, reduces production costs and product scrap rates. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 Schematic diagram of a method for preparing a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure in an embodiment of the present invention.
[0023] Figure 2 Schematic diagram of the basic optimization model structure of the vibration isolation metamaterial structure in Example 1 of the present invention.
[0024] Figure 3 This is a complete production process diagram for directly obtaining formed parts in Examples 1-4 of the present invention.
[0025] Figure 4 The SEM images of the cross-section microstructure of the 3D printed parts at different laser scanning speeds in the embodiment of the present invention; Figure 5 These are optical photographs of the surface microstructure at the same position of the vibration isolation structure frame directly obtained in Example 2 of the present invention: (a) v=600mm / s; (b) v=800mm / s; (c) v=1000mm / s.
[0026] Figure 6 The vibration isolation structure directly obtained in Example 3 of the present invention is experimentally tested to verify the test results of the mechanical properties: (a) load-displacement curves at different scanning speeds; (b) deformation of the vibration isolation structure unit; (c) simplified schematic diagram of the vibration isolation principle.
[0027] Figure 7 These are the experimental results of the low-frequency vibration isolation performance test after directly obtaining the vibration isolation structure in Example 3 of the present invention: (a) the longitudinal band gap of the vibration isolation structure; (b) the simulated harmonic response curve of the vibration isolation structure; (c) the experimentally verified harmonic response curve of the vibration isolation structure.
[0028] Figure 8 1 is an exploded view of a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial device in an embodiment of the present invention.
[0029] Fig. 9 It is a stereoscopic diagram of a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial device in an embodiment of the present invention.
[0030] Fig.10 It is a three-dimensional diagram of the vibration isolation device in the embodiment of the present invention.
[0031] Description of the numbers in the figure: 1. Mass block; 2. Frame structure; 3. Crease unit; 4. First vibration isolation unit; 5. Second vibration isolation unit; 31. Vertical crease; 32. Horizontal crease. DETAILED DESCRIPTION
[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0033] The gas atomized AlSi7Mg alloy powder used in this embodiment is produced by Jiangsu Willari New Materials Technology Co., Ltd., and the particle size range of the powder is 15-53 μm (chemical composition: 92.43at.%, 7.23at.%Si, 0.34at.%Mg). AlSi7Mg is selected as an alloy for LPBF manufacturing because AlSi7Mg has the characteristics of low density and high ductility, and has certain strength and corrosion resistance. Parts made with AlSi7Mg show higher stability and reliability, especially in high-performance mechanical systems for vibration reduction applications. In the experiment, we used the laser powder bed melting equipment DiMetal-100H manufactured by Guangzhou Leijia Additive Technology Co., Ltd. This additive manufacturing printer is equipped with a 300W adjustable ytterbium fiber laser with a spot diameter of 70 μm, and is also equipped with an automatic powder spreading device. The laser powder bed melting device is also equipped with a cooling circulation system (water chiller), a gas filtration circulation system (circulator), a protective gas filling device, and a computer control system for controlling the forming process. In this embodiment, the power of the laser is set to 200 W, the interlayer thickness is 30 μm, the scanning pitch is 60 μm, and the scanning speeds of the laser beam are 600 mm / s, 700 mm / s, 800 mm / s, 900 mm / s, and 1000 mm / s.
[0034] The quasi-static compression test was completed by an electronic universal testing machine (CMT4304-5-KN, SANS Company, China). The sample was placed on the horizontal platform on the base of the testing machine and fixed and leveled by the center of the steel fixture. The test machine applied a uniform downward displacement to the upper surface of the sample through the upper fixture. At the same time, the upper fixture accurately obtained the force applied during the uniform displacement through the sensor, which was equivalent to the upward reaction force during the compression of the vibration isolation metamaterial unit structure. After the compression was completed, the force-displacement curve during the compression process was automatically drawn. The compression speed was set to 1 mm / min. Example
[0035] like Figure 1-10 As shown, in this embodiment, a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure is disclosed, including at least a pair of kite-shaped frame structures of the same size and shape and overlapped front and back, wherein the vertical diagonal of one of the frame structures is provided with a vertical fold, and the transverse diagonal of the other frame structure is provided with a horizontal fold. The middle part of the vertical fold and the horizontal fold has a plurality of fold units in the shape of a "F" distributed in a zigzag shape, and each of the fold units is equal in size. Mass blocks are provided at the upper and lower ends of the frame structure. The upper and lower quadrilateral frames of the kite-shaped frame structure have widths of 20 mm and 40 mm respectively, and the structure is a kite-shaped frame, with two diagonals perpendicular to each other. The upper end is 60° and the lower end is 120°. The thickness of the frame structure, the horizontal fold and the vertical fold are all 1 mm. The decision to select a structural parameter of 1 mm as the frame thickness was based on experiments with early printed specimens, which showed that specimens with a thickness less than 1 mm exhibited poor formability and were more easily damaged when cut from the substrate due to residual stress, while specimens with a thickness exceeding 1 mm showed poor low-frequency absorption and a narrower low-frequency bandgap.
[0036] Specifically, in this embodiment, the method for preparing the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure is formed by a laser 3D printing process, and is characterized by comprising the following steps: S1. Control the oxygen content in the forming cavity to be less than 10 ppm; S2, controlling the powder feeding device to feed the 3D printing metal powder to the forming cylinder, and then using the automatic powder spreading device to evenly spread the aforementioned 3D printing metal powder on the forming substrate; S3, controlling the laser scanning to form the 3D printed metal powder on the substrate until it is completely melted, thereby forming a single-layer cross-section of a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure specimen; the laser line energy scanning speed v of the laser used is between 600 mm / s and 1000 mm / s, and the laser power P is set to a constant value of 200 W; S4. After each layer is processed, the forming cavity is lowered by the thickness of one layer of powder. According to the scanning model of the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, steps S2 and S3 are repeated to finally obtain the target sample formed part.
[0037] More specifically, the method for preparing the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure in this embodiment specifically includes the following steps: (1) The structural parameters were designed and simulated in the simulation software COMSOL, inspired by the deformation movement of the Miura origami tube. The optimal model was determined by the changes in the structural parameters.
[0038] (2) Create a geometric model on a computer, use slicing software to discretize the geometric model into layers, and generate a scanning model from the two-dimensional geometric contour.
[0039] (3) Fix the substrate horizontally on the forming cylinder, adjust the height of the horizontal substrate and the scraper to a suitable position, and ensure that the scraper can smoothly deliver the metal powder into the forming cylinder.
[0040] (4) Open the vacuum pipe and vacuum pump to evacuate to a certain degree, then introduce argon as protective gas into the forming cavity, the concentration of which should not be less than 99.99%. Repeat the evacuation and filling of protective gas three times each, and control the oxygen content in the forming cylinder within the concentration range of 2 ppm; then fix the forming substrate horizontally on the forming cylinder, adjust the height of the horizontal substrate and the powder feeding device to a suitable position, and ensure that the powder feeding device can smoothly feed the metal powder into the forming cylinder.
[0041] (5) Control the powder feeding device to feed the metal powder onto the forming cylinder, and then spread the metal powder evenly.
[0042] (6) The laser passes through the laser emission system and enters the forming chamber from the light outlet. It scans the metal powder according to the previously determined scanning path, completely melts the metal powder, and forms a single-layer cross-section of the sample. The laser spot diameter used at this time is 60 μm. The laser scanning mode is "S-shaped orthogonal stacking" scanning, the laser scanning speed is 600 mm / s; the laser jump speed is 3500 mm / s; the laser power is 200 W; and the scanning interval is 60 μm.
[0043] (7) After each layer is processed, the forming cylinder descends by the thickness of one layer of powder. According to the scanning path in (2), steps (5) to (6) are repeated to melt the metal powder layer by layer, accumulate and bond, and finally obtain the target sample formed part; the height of the forming cylinder descending each time is 25 μm.
[0044] (8) After processing, wait for cooling and take out the product. Embodiments 2 to 5 The present embodiment has some of the same parameters as the first embodiment, except for the laser process parameters in step (6). The laser scanning speeds are 700 mm / s, 800 mm / s, 900 mm / s, and 1000 mm / s respectively; the laser power is kept set at 200 W.
[0045] Corresponding to the following table Combination Figure 4 As shown, Figure 4The SEM images of the cross-sectional microstructures of 3D printed parts at different laser scanning speeds are disclosed. It can be seen that the surface forming quality of the formed samples is different under different v. When the laser scanning speed is 600 mm / s, the vertex surface of the formed quasi-zero stiffness metamaterial has a high density of small holes. In contrast, when the laser scanning speed is 800 mm / s, no obvious holes are observed in the corresponding area of the formed part, and the roughness of the formed surface is low (Ra=24.62 µm). The quasi-zero stiffness vibration isolation structure designed and manufactured by the present invention is composed of multiple thin-walled structures with small-sized geometric features, and the thermal conductivity from the substrate to the formed part is low. Therefore, heat will be lost more slowly through the additively manufactured formed part, and the thermal radiation will react more strongly to the adjacent powder bed, which may cause partial sintering of the powder particles, thereby adversely affecting the density and roughness of the laser 3D printed formed part. Due to the laser scanning strategy and the inertia of laser scanning, the edges of the formed parts tend to overheat, resulting in a more rounded shape at the edges of the formed parts and a thin-walled structure relative to the frame, which enhances the spheroidization effect.
[0046] Further analysis Figure 5 (a) shows that the first fracture point of most quasi-zero stiffness parts is concentrated between the displacement of 13 mm and 14 mm, but there are significant differences in the fracture point positions of parts manufactured at different laser scanning speeds. In particular, when the laser scanning speed is set to 800 mm / s, no obvious fracture occurs in the parts. By comparing the fracture behaviors of samples manufactured at different scanning speeds, the following conclusions can be drawn: The main reason for the change in the position of the first fracture point is the difference in processing parameters, especially the laser scanning speed has an important influence on the mechanical properties of the parts.
[0047] At a laser scanning speed of 800 mm / s, the specimens showed better fracture resistance, indicating that this processing condition helps improve the structural integrity of the quasi-zero stiffness formed parts. Combined with the different loads required for each specimen in the tensile test, it can be inferred that the optimization of the laser scanning speed has a significant effect on the microstructure inside the material, thereby enhancing the toughness and fatigue resistance of the specimens.
[0048] For most quasi-zero stiffness formed parts, Figure 5From the fracture points marked by the red diamond symbol in (a), it can be seen that the second fracture usually occurs between 14 mm and 16 mm in displacement, and similar to the first fracture, the location of the second fracture and the required stress are also highly dependent on the processing parameters of the sample. By comparing and analyzing the stress values of these fracture points, it can be found that the stress value that causes the second fracture is almost the same as the stress value of the first fracture. This shows that after the stress reaches a certain critical value, the formed part will break again within a relatively close displacement range, and this phenomenon shows regularity at different laser scanning speeds.
[0049] It is worth mentioning that the specimens manufactured at a laser scanning speed of 800 mm / s did not show obvious fractures during the entire test process. This phenomenon shows that the laser scanning speed of 800 mm / s optimizes the internal microstructure of the formed part, enhances the continuity and uniformity of the material, and thus improves its durability and fracture resistance. It shows that the material has good toughness and ductility, and can absorb energy without brittle fracture when subjected to external pressure; it can effectively disperse and absorb external impact and vibration energy, and enhance the vibration isolation effect; it can withstand repeated loading in long-term use, showing good fatigue performance and long-term stability; it also shows that the uniformity and consistency of the material have been verified, which helps to improve the feasibility of large-scale production. This result provides an important experimental basis for further optimizing the manufacturing process of quasi-zero stiffness formed parts, especially in application scenarios that require high reliability and high performance. Optimizing the laser scanning speed will become a key factor in improving the quality of formed parts.
[0050] Combination Figure 5 As shown, Figure 5 (a) Load-displacement curves of five groups of quasi-zero stiffness specimens manufactured by laser 3D printing under different laser scanning speeds. When loaded to 12 mm, the displacement curves from top to bottom are 800 mm / s, 700 mm / s, 600 mm / s, 900 mm / s and 1000 mm / s. After loading to a displacement of 3.5 mm, all quasi-zero stiffness units exhibit quasi-zero stiffness behavior until the deformation displacement reaches 5.5 mm. This quasi-zero stiffness mechanism is explained by finite element simulation. Figure 5 The schematic diagram in (b) is a comparison of the compression results in the experiment and the corresponding results of the simulated compression, which were recorded during the compression test at the same loading stage to confirm the results of the finite element method. Figure 5 (b) also uses red arrows to indicate that when the quasi-zero stiffness phenomenon occurs, the displacement of the actual formed part and the displacement trend of the quasi-zero stiffness during compression simulation are highly consistent. To be precise, the horizontal folds and the frame are regarded as an integral structure with negative stiffness, while the vertical folds are regarded as vertical springs that provide constant positive stiffness. Figure 5(c).
[0051] Combination Figure 6 As shown, Figure 6 The surface microstructure diagram at the same position of the vibration isolation structure directly obtained by using the specific embodiment 2 of the laser 3D printing technology. It can be seen that different laser scanning speeds have different effects on the same position. When the laser scanning speed is lower than 600 mm / s, the higher laser energy density effectively overheats the molten pool. The resulting evaporation leads to the formation of keyhole holes in the molten pool constituting the thin-walled structure, and many holes are observed on the surface of the formed part manufactured at 1000 mm / s. The formed part with higher porosity will provide poor tensile properties and may increase the overall stiffness and natural frequency of the vibration isolation system. At the same time, the porosity will make the vibration isolation system unstable and reduce its efficiency in the low-frequency region. The densification level of the low-frequency vibration isolation structure formed part manufactured by laser 3D printing is very sensitive to the applied process parameters. When the laser scanning speed is low (≤600mm / s), the higher laser energy density will cause the molten pool to overheat significantly. Because the metal evaporation caused by the overheating of the molten pool will cause holes to form in the molten pool when forming a thin-walled structure.
[0052] Furthermore, combined with Figure 6 (c) shows the simulated von Mises stress diagram in the quasi-zero stiffness region. At the beginning of the compression process, the load on the vertical crease is greater than that on the horizontal crease and the frame region. As the displacement increases, the increased stress in the vertical crease is transferred to the horizontal crease. Due to this load transfer, the stress remains unchanged along the vertical direction throughout the quasi-zero stiffness structure. The transfer of force is one of the reasons why the structure can achieve quasi-zero stiffness.
[0053] Combination Figure 7 As shown, Figure 7Longitudinal energy bands, simulated harmonic response curves, and harmonic response curves obtained from experimental measurements of low-frequency vibration isolation performance for quasi-zero stiffness formed parts manufactured by laser 3D printing. From the results in the figure, it can be inferred that with appropriate structural parameters, quasi-zero stiffness formed parts with a frame thickness of 1 mm, a top angle of 60°, and a bottom angle of 120° can form ultra-wide low-frequency longitudinal band gaps. There are four longitudinal band gaps in the observed frequency range, where the first, second, third, and fourth band gaps are located between 660 Hz-780 Hz, 1120 Hz-1166 Hz, 1167 Hz-1330 Hz, and 1420 Hz-2570 Hz, respectively. The experimental results also show that metamaterials can attenuate longitudinal waves in an ultra-wide frequency range. Further analysis of the wave modes at different frequencies shows that the wave energy is not only converted into local resonance along the wave vector along the direction, but also forms a rich wave coupling phenomenon, including transverse vibration and lateral vibration, which hinders the propagation of waves. Calculation of the frequency response function (FRF) of quasi-zero stiffness parts manufactured by laser 3D printing[ Figure 7 (b)], the attenuation mechanism of longitudinal waves can be proposed. The results show that the band gap of the metamaterial consists of two parts. In the second part of the band gap, the propagation mode of longitudinal waves in the metamaterial is completely different. In the frequency range of the first part, the longitudinal waves are significantly attenuated. Then, the longitudinal waves are converted into transverse waves in the frequency range of the second part. Finally, the fabricated quasi-zero stiffness formed parts are able to attenuate longitudinal waves in an ultra-wide frequency range, showing quasi-zero stiffness characteristics, such as Figure 7 (c) as shown.
[0054] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0055] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, characterized in that: It comprises at least one pair of kite-shaped frame structures which are consistent in size and shape and overlap front and back, wherein the vertical diagonal line of one of the frame structures is provided with a vertical fold, and the horizontal diagonal line of the other frame structure is provided with a horizontal fold.
2. The quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure according to claim 1, characterized in that: The frame structure and the vertical fold or the horizontal fold are an integrated structure.
3. The quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure according to claim 2, characterized in that: The middle part of the vertical fold and / or the horizontal fold has a plurality of "X"-shaped fold units distributed in a zigzag shape, and each of the fold units has an equal size.
4. The quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure according to claim 1, characterized in that: The frame structure is integrally formed with the vertical fold and the horizontal fold by using additive technology.
5. A quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure according to any one of claims 1 to 4, characterized in that: Mass blocks are arranged at the upper and lower ends of the frame structure.
6. A vibration isolation device, characterized in that: It comprises the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure as described in any one of claims 1-5.
7. The vibration isolation device according to claim 6, characterized in that: A plurality of the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structures are connected end to end from top to bottom to form a group of vibration isolation structures, and a plurality of groups of the vibration isolation structures are combined to form a vibration isolation device.
8. A method for preparing a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, formed by a laser 3D printing process, characterized in that: The following steps are involved: S1. Control the oxygen content in the forming cavity to be less than 10 ppm; S2, controlling the powder feeding device to feed the 3D printing metal powder to the forming cylinder, and then using the automatic powder spreading device to evenly spread the aforementioned 3D printing metal powder on the forming substrate; S3, controlling the laser scanning to form the 3D printed metal powder on the substrate until it is completely melted, thereby forming a single-layer cross-section of a quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure specimen; the laser line energy scanning speed v of the laser used is between 600 mm / s and 1000 mm / s, and the laser power P is set to a constant value of 200 W; S4. After each layer is processed, the forming cavity is lowered by the thickness of one layer of powder. According to the scanning model of the quasi-zero stiffness nonlinear low-frequency vibration isolation metamaterial structure, steps S2 and S3 are repeated to finally obtain the target sample formed part.
9. The preparation method according to claim 8, characterized in that: In step S3, the laser scanning mode is "S-shaped orthogonal" scanning, the laser scanning speed is 600~1000 mm / s; the laser jump speed is 3000~3500 mm / s; the laser power is 200 W; and the scanning interval is 60~80μm.
10. The preparation method according to claim 8, characterized in that: The 3D printing metal powder is gas atomized AlSi7Mg alloy powder, and the particle size range of the powder is 15-53 μm.
Citation Information
Cited By
Inertia amplification non-linear low-frequency vibration isolation metamaterial structure based on additive manufacturing, vibration isolation device and performance regulation and control method of inertia amplification non-linear low-frequency vibration isolation metamaterial structure
CN122083091A